Panpipes and the equiheptatonic pitch - Jones, A. M. (International Library of African Music, 1980)
The purpose of this paper is twofold: firstly to explain a method of transcribing African instrumental music, and secondly to give information on the structure of the Mangwilo xylophone music of the Alomwe and Ashirima in Northern Mozambique.
Keywords: African Music